CHLA Standards for Library and Information Services in Canadian Health & Social Services Institutions 2020 - Francesca Frati; Lori Anne Oja; Julia Kleinberg (Journal of the Canadian Health Libraries Association, 2021)
The following standards, with supporting evidence, are intended to serve as a guide to structuring minimum library services within health and social services institutions across all Canadian provinces and territories. The Standards are not intended to be aspirational. The aim of the Canada Health Libraries Association (CHLA) Task Force was to ensure that the Standards update would not be so removed from the current realities and landscape that they became unattainable to many libraries. For this reason, some Standards outline requirements that are essential to the minimum function of the library, and other Standards provide recommendations only. The intended use of the Standards is to set a baseline for the provision of essential library services and resources and aid in advocating for adequate resources. It is important to note, however, that the CHLA Task Force does not intend for the Standards to prevent libraries from reaching a more advanced level of service, and we hope that in their current form they will not be a hindrance to excellence or innovation.